PolySialic acid-nanoparticles inhibit macrophage mediated inflammation through Siglec agonism: a potential treatment for age related macular degeneration - Krishnan, Anitha; Sendra, Victor G.; Patel, Diyan; Lad, Amit; Greene, Michelle K.; Smyth, Peter; Gallaher, Samantha A.; Herron, Úna M.; Scott, Christopher J.; Genead, Mohamed; Tolentino, Michael (Frontiers in Immunology, 2023)
Age-related macular degeneration (AMD) is a chronic, progressive retinal disease characterized by an inflammatory response mediated by activated macrophages and microglia infiltrating the inner layer of the retina. In this study, we demonstrate that inhibition of macrophages through Siglec binding in the AMD eye can generate therapeutically useful effects. We show that Siglecs-7, -9 and -11 are upregulated in AMD associated M0 and M1 macrophages, and that these can be selectively targeted using polysialic acid (PolySia)-nanoparticles (NPs) to control dampen AMD-associated inflammation. In vitro studies showed that PolySia-NPs bind to macrophages through human Siglecs-7, -9, -11 as well as murine ortholog Siglec-E. Following treatment with PolySia-NPs, we observed that the PolySia-NPs bound and agonized the macrophage Siglecs resulting in a significant decrease in the secretion of IL-6, IL-1β, TNF-α and VEGF, and an increased secretion of IL-10. In vivo intravitreal (IVT) injection of PolySia-NPs was found to be well-tolerated and safe making it effective in preventing thinning of the retinal outer nuclear layer (ONL), inhibiting macrophage infiltration, and restoring electrophysiological retinal function in a model of bright light-induced retinal degeneration. In a clinically validated, laser-induced choroidal neovascularization (CNV) model of exudative AMD, PolySia-NPs reduced the size of neovascular lesions with associated reduction in macrophages. The PolySia-NPs described herein are therefore a promising therapeutic strategy for repolarizing pro-inflammatory macrophages to a more anti-inflammatory, non-angiogenic phenotype, which play a key role in the pathophysiology of non-exudative AMD.